Plasma levels of alpha-fetoprotein and carcinoembryonic antigen in patients with malignant gastrointestinal tumors. - Monteiro, J C; Moreira, M M; Pereira, F E; de Oliveira, L R; da Cunha, E A; Leite, J F; Castro e Sousa, F (Acta Médica Portuguesa, 1989)
Levels of alpha-fetoprotein (AEP) and carcinoembryonic antigen (CEA) were determined in the plasma of 142 patients with malignant gastrointestinal tumours. AEP was raised in only four patients (2.8%); two patients with carcinoma of the stomach showed relatively elevated levels. Abnormal CEA levels were found in 82 patients (57.7%). The patients' age with positive CEA levels was a greater than that of the patients with normal levels (p less than 0.05). In patients with gastric tumours CEA positivity was correlated with clinico-pathological stage (pTNM) and with the resectability rate (p less than 0.05). In patients with carcinoma of colon and rectum a greater incidence of elevated plasma CEA levels, as well as higher levels, were found in patients with carcinoma of the left colon than in those with right colon tumours. Statistically significant differences were found between the positivity rate and Dukes' grading (p less than 0.05), as well as between CEA levels in Dukes' stages C and 'D' (p less than 0.005). It is concluded that AFP has a very limited clinical role in patients with malignant extra-hepatic gastrointestinal tumours and that CEA may have a clinical role in tumours of the digestive tract, other than carcinoma of colon and rectum.